Prevalence of ADHD Symptomatology in Adult Population in the Czech Republic–A National Study. Issue 12 (October 2021) - Vňuková, Martina; Ptáček, Radek; Děchtěrenko, Filip; Weissenberger, Simon; Ptáčková, Hana; Braaten, Ellen; Raboch, Jiří; Anders, Martin; Klicperová-Baker, Martina; Goetz, Michal
Background: Attention deficit/hyperactivity disorder is a common neurodevelopmental disorder frequently diagnosed between the ages 7 and 10 years. We measured ADHD symptomatology in a representative sample of the Czech population.Material and Methods: Data collection was performed in January 2019 through the European National Panel. The respondents completed a demographic questionnaire focusing on ADHD history and a standardized questionnaire, the Adult ADHD Self-Report Scale (ASRS) screener for ADHD symptomatology in adulthood.Results: From the sample of 1, 518 respondents, 3% of the respondents reported having been diagnosed with ADHD/hyperkinetic disorder in their lifetime. According to ASRS scoring, 119 respondents were classified as suspected ADHD. Overall, more males than females reported ADHD symptomatology. Age was also significantly associated with ASRS. Education status yielded no significant results.Conclusion: Our study documents that the prevalence of ADHD symptomatology in adults is comparable with that in Western countries despite the different historical and health care backgrounds.